Nível de atividade física e qualidade de vida em amputados de membro inferior no município de Aracaju-SE - Lima, Rafael Araújo dos Santos (2015)
Amputation is the total or partial loss of a member, surgically or by trauma, causing physical, psychological and social damage that can cause a reduction of qualify of life. The increased physical activity has been recommended both by its physical effects as psychological and social benefits. However lower limb amputees have lower levels of physical activity, in addition to having features that can change the relationship between quality of life and physical activity. The objective of this study was to determine the factors related to the practice of physical activity and quality of life of subjects lower limb amputees. A cross-sectional study was conducted using a form sociodemographic and clinical, a questionnaire of quality of life, the WHOQOL-BREF, another, the IPAQ, about physical activity, and mobility was evaluated by LCI. For statistical analysis, the Shapiro-Wilk test were used, chi-square, Student t and Mann-Whitney (p <0.05). Within the overall sample physical activity was correlated only with the physical of quality of life. We found also significant differences between the psychological domain and the quality of life overall, when we make compared between genders. To the sample just with amputees prothetizades, we observed a significant difference between the psychological and social domains relationship in relation to the environment domain, this being repeated also among prothetizades amputees considered active. In this research, the physical activity demonstrated to have impact only on the physical domain of quality of life. And on prothetizades the quality of life did not seems to be influenced by the level of physical activity .